2013
DOI: 10.2528/pier13052607
|View full text |Cite
|
Sign up to set email alerts
|

Four-Band Polarization-Insensitive Metamaterial Absorber Based on Flower-Shaped Structures

Abstract: Abstract-In this paper, a four-band metamaterial absorber (MA) based on flower-shaped structure is proposed. The design, simulation, fabrication, and measurement of the absorbers working in four bands are presented. Simulation results show that the MA has four distinctive absorption peaks at frequencies 6.69 GHz, 7.48 GHz, 8.67 GHz, and 9.91 GHz with the absorptivity of 0.96, 0.99, 0.99 and 0.98, respectively. Experiment results matches well with the simulation. Both experiment and simulation results exhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Nowadays, microwave absorbers have been extensively investigated from few gigahertz to optical frequency ranges for various potential applications. In the past few years, significant research has been carried out in the design of single band, dual band, and multiband . Author Dincer et al analyzed the properties of single band absorber theoretically, numerically, and experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, microwave absorbers have been extensively investigated from few gigahertz to optical frequency ranges for various potential applications. In the past few years, significant research has been carried out in the design of single band, dual band, and multiband . Author Dincer et al analyzed the properties of single band absorber theoretically, numerically, and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al, and Asgharian et al, reported compact metamaterial absorbers, however, the perfect absorption is not achieved. Moreover, number of researchers explored various multiband polarization insensitive absorbers in References , however the size, absorption rate, and thickness are still scope of improvement. Furthermore, authors were also working on the broadband absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], an ultra thin and triple-band metamaterial radar absorber is designed and experimentally investigated. A four-band metamaterial absorber based on flower-shaped structure is proposed in [14]. Dincer et al designed a dual-band metamaterial absorber based on isotropic resonator [15].…”
Section: Introductionmentioning
confidence: 99%
“…The multiple-band MPAs can be easily obtained by coplanar or stacked structures composed of several different dimensions of the metallic elements (or resonators)272829303132333435363738394041424344454647484950515253. However, because the limitation of the number of the resonators or elements in the metamaterial structures, the research of the multiple-band MPAs is mainly concentrated in dual-band2728293031323334, triple-band3536373839404142 and quad-band absorption4344454647484950515253.…”
mentioning
confidence: 99%
“…However, because the limitation of the number of the resonators or elements in the metamaterial structures, the research of the multiple-band MPAs is mainly concentrated in dual-band2728293031323334, triple-band3536373839404142 and quad-band absorption4344454647484950515253. In other words, the number of the absorption peaks of the current MPAs is no more than four.…”
mentioning
confidence: 99%